(untitled) (University Heart Journal, 2009)
Trimetazindine MR in Patients with Stable Angina in Bangladesh TRIUMPH-BANGLA Study Group MN ISLAM, MA BASHAR, RS MAHMUD, N FARID, AW CHOWDHURY, KHQ ISLAM, MS BARI, SC DHAR, MS HOQUE, MT RAHMAN, AK CHOUDHURY, TC GHOSE, PK DAS, TF KAHN January 2008, Vol. 4. Number I, Page 9-13. Several printing mistakes was detected after printing the article. A corrected version of the article has been published as reprint. Editor